1995
DOI: 10.2134/jeq1995.00472425002400040025x
|View full text |Cite
|
Sign up to set email alerts
|

Late Fall Site‐Specific Soil Nitrate Upper Limits for Groundwater Protection Purposes

Abstract: For temperate regions, such as Germany, a simple management model is developed, with which NO3 seepage losses during winter can be estimated, when the amount and distribution of soil NO3 in late fall are known. The semi‐analytical, one‐dimensional model is developed for homogeneous soils. The model is derived for steady‐state flow conditions at a constant soil water content (field capacity). Essential part of the model is a solute transport equation based on mixing‐cell theory. Sample calculations show that wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

1995
1995
2006
2006

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 0 publications
1
15
0
2
Order By: Relevance
“…In LIXIM, the layer thickness has been taken as z = 1 cm, which would correspond to the dispersivity λ = 0.5 cm. We checked that the transport submodel of LIXIM gave similar results to those published by Van der Ploeg et al . (1995) with this dispersivity.…”
Section: The Modelsupporting
confidence: 74%
See 2 more Smart Citations
“…In LIXIM, the layer thickness has been taken as z = 1 cm, which would correspond to the dispersivity λ = 0.5 cm. We checked that the transport submodel of LIXIM gave similar results to those published by Van der Ploeg et al . (1995) with this dispersivity.…”
Section: The Modelsupporting
confidence: 74%
“…Using the terminology defined by Addiscott & Wagenet (1985), the water and solute leaching submodel in LIXIM is a ‘deterministic functional model with a layer approach’. It is derived from the approach proposed by Burns (1974) and the ‘mixing‐cells’ concept developed by Van Ommen (1985) and Van der Ploeg et al . (1995) for nitrate movement.…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the approach differs from that used by van der Ploeg et al (1995), who approximated the spatial derivatives by finite differences and integrated over time whereas in this present approach time is differenced and space is continuous.…”
Section: Numerical Scheme To Solve the Differential Equationsmentioning
confidence: 95%
“…In temperate regions, solute leaching occurs predominately in the winter period when soils are approximately at field capacity. Consequently, water-flow conditions may be characterized as nearly steady-state (van der Ploeg et al, 1995). It has been shown that under such conditions, the convection-dispersion equation (CDE) yields comparable results to more comprehensive transient models if solute leaching is considered as a function of cumulative infiltration (Wierenga, 1977).…”
Section: Introductionmentioning
confidence: 99%